Pengaruh Inflasi dan Nilai Tukar Rupiah Terhadap Nilai Aktiva Bersih Reksadana Syariah - Adrian, Muhammad; Rachmawati, Lucky (Universitas Negeri Surabaya, 2019)
This research was conducted to analyzeweather inflation and rupiah exchange rate have an influence on the NAV Islamic mutual funds. Data used in this research is monthly statistical data ranged from 2015 until 2017. This research used multiple linear resgression analysis with T-test, F-test and R Square. The result of this research shows that partially, inflation has a relevant influence towards NAV Islamic mutual funds and rupiah exchange hasn’t a relevant influence towards NAV Islamic mutual funds. While simultaneously, inflation and rupiah exchange hasn’t relevant influence towards NAV Islamic mutual funds